The effect of sports anxiety on the level of achievement of Archery players in Syrian Arab Republic - حمدان عيسى; ريم محمد سلمان (Latakia University Journal -Medical Sciences Series, 2024)
Sports anxiety is an important factor that may affect the achievement level in competitive sports like Archery. The study aimed at Knowing the effect of sport anxiety on achievement of Archery players. The study conducted on a sample of (11) male and female players from 15 - 17 years old out of (15) who participated in Archery competition in Syrian Arab Republic 2023. The study was applied in Al-Assad Sport city (indoor halls). The descriptive approach was used and the sports anxiety questionnaire which was designed by (KAFAFY, et al., 1985) and shooting test to identify the level of playersʼs achievement, due to its agreeability to the nature of this research. The arithmetic standard deviation, Cronbach’s Alpha, Mann-Whitney test, Wilcoxon Test, T test and Pearson correlation coefficient were used. As a result, it was concluded that there is a weak adverse correlation between the variables of sports anxiety and achievement level.